Erratum: delos Angeles, M.D., Rubite, R.R., Chung K.F., Buot, I.E. Jr. & Tandang, D.N. (2022) Begonia normaaguilariae (section Baryandra, Begoniaceae), a new species from the limestone forests of Samar Island, Philippines. Phytotaxa 541 (1): 49–56. - Delos Angeles, Marjorie D.; Rubite, Rosario R.; Chung, Kuo-Fang; Buot Jr., Inocencio E.; Tandang, Danilo N. (Phytotaxa, 2024)
N/A